Theorem about spin splitting of energy levels within Kildal-Bondar model - Dvornik, O.V.; Chuiko, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The semiconductor Cd₃As₂ is known as a zero-gap material like HgTe or α-Sn
but with the tetragonal lattice and in various crystalline forms. One of the forms has no
symmetry center, and just this form is stable under ordinary conditions. So, every of its
energy bands is split into a pair of spin subbands owing to the removal of the Kramers
degeneration. The theory predicts that the total sum of all spin splittings will be equal to
zero, whereas the modeling shows the peculiar dependences of spin splittings on the
direction and modulus of the wave vector.